Advancing Zero-Carbon Cities through Urban Green Infrastructure in Karaj, Iran - Salimi, Mahsa; Kafi, Mohsen; Khansefid, Mahdi (Alanya Üniversitesi, 2025)
Urban areas in semi-arid regions face rising thermal stress and carbon emissions due to rapid densification and scarce vegetation. This study evaluates the effectiveness of green infrastructure (GI) in mitigating these challenges in District one of Karaj, Iran, within a zero-carbon city framework. To address limited evidence on microscale modeling in arid contexts, satellite-based time series analysis was combined with ENVI-met simulations. Environmental indicators including CO (Sentinel-5P) as a proxy for CO₂, Land Surface Temperature (LST, Landsat-8), and vegetation cover (NDVI, MODIS) were extracted via Google Earth Engine for October 2024 to March 2025. Two scenarios were examined: Scenario A as current conditions, and Scenario B with green roofs, vegetated walls, moss, and microalgae panels. Scenario B achieved a 4.6% reduction in CO₂, from 441.8 to 421.4 ppm, an NDVI increase of 0.17 (0.21 to 0.38), and a district-wide temperature decrease of 4.1 °C. Calibration yielded a root mean square error of 1.7 °C for temperature and ±6.3 ppm for CO₂. These interventions improve environmental performance and socio-economic resilience through public health gains, lower energy costs, and equitable green access. Findings highlight hybrid greening strategies as effective for advancing climate resilience and provide a replicable model for zero-carbon interventions in semi-arid cities.